First, recognize that x is a factor of every term. This means the equation can be written as

x(x^2 - 6x + 7) = 0

Among other things, this means that

The quadratic term does not factor nicely, so the zeros of it can be found using the quadratic formula.

= (-(-6)±√((-6)^2 - 4*1*7))/(2*1)

= (6 ±√(36-28))/2

x(x^2 - 6x + 7) = 0

Among other things, this means that

**x = 0**is a solution to the equation.The quadratic term does not factor nicely, so the zeros of it can be found using the quadratic formula.

**x = (-b±√(b^2-4ac))/(2a)**= (-(-6)±√((-6)^2 - 4*1*7))/(2*1)

= (6 ±√(36-28))/2

**x = 3 ± √2**(These are the other two solutions.)